Serum Neurofilament Light Chain Levels May Be a Marker of Lower Motor Neuron Damage in Amyotrophic Lateral Sclerosis - Zhang, Linjing; Ji, Tuo; Wu, Chujun; Zhang, Shuo; Tang, Lu; Zhang, Nan; Liu, Xiangyi; Fan, Dongsheng (Frontiers in Neurology, 2022)
Objectives The aims of this study were to investigate whether serum neurofilament light chain (NfL) levels were correlated with the severity of axonal degeneration of lower motor neurons (LMNs) in the early symptomatic phase of amyotrophic lateral sclerosis (ALS). Methods In this prospective, serum samples used for NfL measurement were obtained from 103 sporadic ALS outpatients within 2-year disease durations. Severity of axonal degeneration was assessed by the decrease in the compound muscle action potentials (CMAPs) within a 1-month interval from serum sampling. Results The NfL levels showed a significant positive correlation with the relative score as a proxy for axonal damage of LMNs in patients with ALS (co-efficient: 0.264, p=0.009). Further, this correlation became stronger (co-efficient: 0.582, p = 0.037) when estimated only among patients with pure LMN involvement subtypes-that is FAS or FLS. The levels of NfL increased with the severity of axonal damage of LMNs (F=6.694, P = 0.0001). Conclusions The serum levels of NfL could mirror the severity of axonal degeneration of LMNs, particularly in patients with signs of predominant LMN involvement. It may have a profound effect on the selection of patients and monitoring treatment efficacy in future disease-modifying clinical trials.